Gaps in measles vaccination coverage in Kasese district, Western Uganda: results of a qualitative evaluation - Walekhwa, Abel Wilson; Musoke, David; Nalugya, Aisha; Biribawa, Claire; Nsereko, Godfrey; Wafula, Solomon Tsebeni; Nakazibwe, Brenda; Nantongo, Mary; Odera, Doreen Awino; Chiara, Achangwa; Boyce, Ross Mathew; Mulogo, Edgar Mugema (BMC infectious diseases, 2022)
Background: Despite the availability of a highly effective vaccine, measles remains a substantial public health problem in many countries including Uganda. In this study, conducted between June–August 2020 following a local outbreak, we sought to explore the factors that could affect measles vaccination coverage in rural western Uganda. Methods: We conducted a descriptive study using qualitative data collection approaches in the Kasese district. The research team utilized purposive sampling to identify and select participants from the public health sector and district government. We conducted key informant interviews (KII) and one focus group discussion (FGD). Responses were recorded using portable electronic devices with the FGD and KII guide installed. Interviews were conducted at the health centre and district headquarters. Data was coded and analysed using ATLAS.ti version 8 software through deductive thematic analysis to identify key themes. Results: Barriers to measles vaccination identified in this study were premised around six themes including: (i) avail ability of supplies and stock management, (ii) health worker attitudes and workload, (iii) financing of vaccination outreach activities, (iv) effectiveness of duty rosters (i.e., health workers’ working schedules), (v) community beliefs, and (vi) accessibility of healthcare facilities. Respondents reported frequent vaccine supply disruptions, lack of resources to facilitate transportation of health workers to communities for outreach events, and health centre staffing that did not adequately support supplemental vaccination activities. Furthermore, community dependence on traditional medicine as a substitute for vaccines and long distances traveled by caregivers to reach a health facility were mentioned as barriers to vaccination uptake. Conclusions: Health system barriers limiting vaccination uptake were primarily logistical in nature and reflect inadequate resourcing of immunization efforts. At the same time, local beliefs favoring traditional medicine remain a persistent cultural barrier. These findings suggest an urgent need for more efficient supply management practices and resourcing of immunization outreaches in order to achieve the Uganda Ministry of Health’s targets for childhood immunization and the prevention of disease outbreaks.
Keywords: Measles; Vaccination; Barriers; Rural district; Uganda